TRANSFORMASI PERAN IBU RUMAH TANGGA MENJADI WOMAN DIGIPRENEUR MELALUI PELATIHAN AFFILIATE MARKETING - Purbasari, Ratih; Sukmadewi, Rani; Muttaqin, Zaenal; Kahfi, Arbi Abdul (Universitas Padjadjaran, 2026)
The rapid growth of the digital economy has created opportunities for women to participate in entrepreneurship; however, housewives in Cikeruh Village still face constraints in digital literacy, creativity, and access to online marketing skills. This community service initiative aimed to transform the role of housewives into women digital entrepreneurs through structured training in affiliate marketing. The program integrated theoretical explanations, interactive discussions, and hands-on practices in producing persuasive promotional content using digital platforms. Data were collected using pre- and post-training questionnaires and analyzed using descriptive quantitative analysis through percentage comparison, complemented by descriptive qualitative analysis from participant feedback. These data were used to measure participants’ progress in entrepreneurial mindset, digital literacy, and content creation skills. The findings revealed significant improvement in participants’ ability to design engaging digital content, increased confidence in managing online business activities, and enhanced understanding of affiliate-based income generation. The training not only built essential entrepreneurial competencies but also fostered awareness of women’s economic potential in the village context. In conclusion, the program successfully strengthened the digital capabilities and independence of women entrepreneurs, promoting inclusive and sustainable community empowerment through technology-based entrepreneurship.Pertumbuhan ekonomi digital yang pesat membuka peluang bagi perempuan untuk berpartisipasi dalam kewirausahaan, namun ibu rumah tangga di Desa Cikeruh masih menghadapi keterbatasan literasi digital, kreativitas, dan kemampuan pemasaran daring. Program pengabdian kepada masyarakat ini bertujuan mentransformasi peran ibu rumah tangga menjadi wirausaha digital wanita melalui pelatihan terstruktur mengenai pemasaran afiliasi. Kegiatan dirancang dengan menggabungkan penjelasan teori, diskusi interaktif, serta praktik langsung pembuatan konten promosi persuasif berbasis digital. Data dikumpulkan melalui kuesioner pre-test dan post-test, kemudian dianalisis menggunakan analisis kuantitatif deskriptif melalui perbandingan persentase, serta didukung oleh analisis kualitatif deskriptif berdasarkan umpan balik peserta. Data digunakan untuk menilai peningkatan pola pikir kewirausahaan, literasi digital, dan keterampilan pembuatan konten peserta. Hasil menunjukkan adanya peningkatan signifikan dalam kemampuan peserta merancang konten digital yang menarik, peningkatan kepercayaan diri dalam mengelola usaha daring, serta pemahaman lebih baik mengenai mekanisme pendapatan berbasis afiliasi. Pelatihan ini tidak hanya membangun kompetensi kewirausahaan yang esensial, tetapi juga menumbuhkan kesadaran akan potensi ekonomi perempuan di tingkat desa. Dengan demikian, program ini berhasil memperkuat kapasitas digital dan kemandirian ekonomi perempuan, sekaligus mendorong pemberdayaan masyarakat yang inklusif dan berkelanjutan melalui kewirausahaan berbasis teknologi.